The effect of dietry vitamin E supplementation on semen quality of A.I. dairy bulls - Webb, E.C. (Edward Cottington) (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Animal Production Management))--University of Pretoria, 2006.